What patients want to know about genetic testing for kidney disease - Savige, Judy; Weinstock, B. André (Frontiers in Medicine, 2023)
Previously, genetic kidney disease was often recognised when family members shared clinical features. Now, many genetic kidney diseases are diagnosed when testing demonstrates a pathogenic variant in a gene associated with the disease. Detection of a genetic variant also identifies the mode of inheritance, and suggests family members at risk. The genetic diagnosis has additional advantages for patients and their doctors even when no specific treatment is available since it often indicates likely complications in other organs, the clinical course, and management strategies. Generally, informed consent is required for genetic testing because the result provides ‘certainty’ with implications for the patient, and their family, and possibly for employment, and for life and medical insurance, as well as having social, ethical, and financial consequences. Patients want to be provided with a copy of their genetic test result in a format that is comprehensible and to have the result explained. Their at-risk family members should be sought out and offered genetic testing too. Patients who allow the sharing of their anonymised results in a registries help advance everyone’s understanding of these diseases and expedite a diagnosis in other families. Patient support groups not only help normalise the disease but also educate patients, and update them on recent advances and new treatments. Some registries encourage patients to themselves submit their genetic variants, clinical features and response to treatment. More and more often, patients may volunteer for clinical trials of novel therapies including some that depend on a genetic diagnosis or variant type.